Identifying Personality Subtypes Based on the Five-Factor Model Dimensions in Male Prisoners: Implications for Psychopathy and Criminal Offending. (January 2014) - Claes, Laurence; Tavernier, Geert; Roose, Annelore; Bijttebier, Patricia; Smith, Sarah Francis; Lilienfeld, Scott O.
The current study was designed to identify personality subtypes on the basis of the five-factor model dimensions in male prisoners. Participants included 110 Flemish male prisoners assessed by means of the Neuroticism, Extraversion, Openness Five Factor Inventory and different symptom, personality, and coping measures. We found two clusters: an emotionally stable/resilient cluster and an aggressive/undercontrolled cluster. Prisoners within the aggressive/undercontrolled cluster scored significantly higher on almost all Minnesota Multiphasic Personality Inventory–2 basic scales, (in)direct aggression measures, and depressive coping scales compared with resilients. They also scored higher on drug abuse and committed more sexual offenses than resilient prisoners. These two personality subtypes bear theoretically and practically important implications for psychopathy subtypes and different pathways to criminal offenses.